If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(1 + -2u) = 2(u + 2) (1 * 4 + -2u * 4) = 2(u + 2) (4 + -8u) = 2(u + 2) Reorder the terms: 4 + -8u = 2(2 + u) 4 + -8u = (2 * 2 + u * 2) 4 + -8u = (4 + 2u) Add '-4' to each side of the equation. 4 + -4 + -8u = 4 + -4 + 2u Combine like terms: 4 + -4 = 0 0 + -8u = 4 + -4 + 2u -8u = 4 + -4 + 2u Combine like terms: 4 + -4 = 0 -8u = 0 + 2u -8u = 2u Solving -8u = 2u Solving for variable 'u'. Move all terms containing u to the left, all other terms to the right. Add '-2u' to each side of the equation. -8u + -2u = 2u + -2u Combine like terms: -8u + -2u = -10u -10u = 2u + -2u Combine like terms: 2u + -2u = 0 -10u = 0 Divide each side by '-10'. u = 0.0 Simplifying u = 0.0
| 2y=6y-11 | | 6x-4=32-3x | | 43X=8X+1 | | -5x^4+20x^3+60x^2=0 | | 40+3r=-7r+4(8r-1) | | p/1.52=-3,600 | | 2x^2+22x+12=9x+6 | | 3-x-5=7 | | 46+4e=8e+14 | | 32X+3=625 | | -2x+6=4x-6 | | -3w+45=2w | | 0=15+3y | | 13j-100=7j-274 | | x^2+10=3x-3 | | -6b+5+2b=25 | | 5x=15+0 | | 5a-6=-(6-6a)-a | | 5(x+3)=2x-3x | | e/0.76=2,809 | | 3(a-a)+2(a-a)-3(2a-3a)= | | 5x-8=3y | | 6x^2-5=x-4 | | -3(2y+7)=-39 | | -42+11x=-7y | | 5.4x-8.3=14.8 | | 5X+2(x-1)=3x+4x+15 | | -2-3(4-4r)=-50 | | k/1.2=-0.07 | | .333y+11=.5y-3 | | x^2+6x+3=-6 | | 2.3(m)+m=26.4 |